1990
DOI: 10.1007/bf01912084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different additives on the thermal decomposition of ammonium perchlorate

Abstract: IR spectral investigations on ammonium perchlorate (AP) in the presence of varying amounts of ammonium permanganate (APm) and 2% by weight of different rare earth oxide additives were made over the temperature range 25-290 ~ Heating and spectral scanning were done simultaneously and the peak intensity was presumed to be proportional to the amount of undeeomposed AP. Presence of 10% APm lowered the temperature of AP decomposition from 200 to I10 ~ and increased the rate by several folds. Mixed oxide produced as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Ammonium perchlorate (AP) is one of the most common energetic material and oxidizer in CSPs. The thermal decomposition of AP plays a significant role in the burning behavior of propellants [2][3][4]. The characteristics of the thermal decomposition of AP are believed to influence the performance of CSPs and remarkably sensitive to additives [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium perchlorate (AP) is one of the most common energetic material and oxidizer in CSPs. The thermal decomposition of AP plays a significant role in the burning behavior of propellants [2][3][4]. The characteristics of the thermal decomposition of AP are believed to influence the performance of CSPs and remarkably sensitive to additives [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium perchlorate (AP) is one of the most common energetic material and oxidizer in composite solid propellants with its content in 60%-80% wt, and the thermal decomposition of AP plays a significant role in the burning behavior of propellants [1][2][3]. Although the characteristics of AP thermal decomposition can be improved to some extent by reducing the particle size of AP, decreasing the particle size of AP is a dangerous process [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chandru et al (2012) synthesized b-MnO 2 and found that mesoporous b-MnO 2 is an excellent catalyst, lowering the HTD from 426.3 to 301 C. 14 The effect of the shape and size of CuO and CoFe 2 O 4 on the thermal decomposition of AP was also studied and a signicant impact was observed on the decomposition pattern of AP. [15][16][17][18][19][20][21] In previous research, copper chromite (CuO$CuCr 2 O 4 ), [22][23][24] ACR and titanium oxide (TiO 2 ) 25,26 have been the most utilized metal oxide catalysts which have considerably decreased the onset temperature of AP decomposition when used individually as additives.…”
Section: Introductionmentioning
confidence: 99%